KOMUNITAS-SEMINARI DIASPORA DALAM MASA PANDEMIC COVID-19 (Reaktif-Reflektif Atas Yoh 20:17) - Donatus Dole (Aggiornamento, 2020)
The timing of the outbreak was never suspected. Likewise, the vocation. Both will appear by themselves and suddenly. There is a big difference betwen, that the outbreak is expected to disappear quickly but the vocation are expected to be maintained. For this reason, the community of Interdiocesan Major Seminary